2021
DOI: 10.3390/s21248341
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Training and Collaboration Integrated Framework for Human–Agent Teleoperation

Abstract: Human operators have the trend of increasing physical and mental workloads when performing teleoperation tasks in uncertain and dynamic environments. In addition, their performances are influenced by subjective factors, potentially leading to operational errors or task failure. Although agent-based methods offer a promising solution to the above problems, the human experience and intelligence are necessary for teleoperation scenarios. In this paper, a truncated quantile critics reinforcement learning-based int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In recent years, the concept of MWL has been researched in several domains to understand the performance limits of humans. For instance, researchers have found that teleoperation tasks cause a trend of an increased MWL that is usually affected by subjective factors [ 7 ]. The increase in the MWL can potentially lead to errors, leading to failure in task completion.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the concept of MWL has been researched in several domains to understand the performance limits of humans. For instance, researchers have found that teleoperation tasks cause a trend of an increased MWL that is usually affected by subjective factors [ 7 ]. The increase in the MWL can potentially lead to errors, leading to failure in task completion.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of data-driven approaches for robot manipulation [12,18], there is a growing need to collect human demonstrations in robotics. To enable easy and scalable data collection, teleoperation has also gained attention in simulated environments [60,32,56,14,8].…”
Section: Related Workmentioning
confidence: 99%
“…A supervised teleoperation scheme can allow the robot to follow human commands [1]- [3]. Similarly, the robotic agent of [4] assists in trajectory training for novices based on task-dependent reinforcement learning. From a cognitive perspective, robots could be made more flexible and better interact with human users by learning from human movements humans using logical inference.…”
Section: Introductionmentioning
confidence: 99%